2019
DOI: 10.1039/c9cc02123j
|View full text |Cite
|
Sign up to set email alerts
|

Electron-pair bonding in real space. Is the charge-shift family supported?

Abstract: Charge-shift bonding (CSB) has been introduced as a distinct third family of electron-pair links that adds to the covalent and ionic tradition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…There is nothing in these profiles that suggests that CSBs are simply stretched covalent bonds,a sa rgued recently. [64] Thus,a tl ong distances,t he Laplacian for HÀHi sv irtually zero,a nd in the range near the equilibrium distance, R = 2-0.75 ,itdescends rather fast and becomes strongly negative, as expected for ac ovalent bond. In contrast, the respective Laplacian curve for FÀFc ontinuously rises from zero at the interval 4.5-3.0 ,r eaching am aximum positive value near the equilibrium distance of the bond, as expected for aC SB dominated by Pauli repulsion.…”
Section: Laplacian Profiles For Csb and Covalent Bondsmentioning
confidence: 78%
See 3 more Smart Citations
“…There is nothing in these profiles that suggests that CSBs are simply stretched covalent bonds,a sa rgued recently. [64] Thus,a tl ong distances,t he Laplacian for HÀHi sv irtually zero,a nd in the range near the equilibrium distance, R = 2-0.75 ,itdescends rather fast and becomes strongly negative, as expected for ac ovalent bond. In contrast, the respective Laplacian curve for FÀFc ontinuously rises from zero at the interval 4.5-3.0 ,r eaching am aximum positive value near the equilibrium distance of the bond, as expected for aC SB dominated by Pauli repulsion.…”
Section: Laplacian Profiles For Csb and Covalent Bondsmentioning
confidence: 78%
“…Of course,o pposite points of view have appeared and suggested that:1 )CSBs are merely covalent bonds,w hich exhibit the same orbital shrinkage and kinetic-energy-lowering in the bonding region as in H À H, [84] and 2) positive Laplacians simply typify long covalent bonds;hence,the long F-F bond is merely astretched covalent bond with apositive Laplacian, and the same would be found if we were to stretch HÀH. [64] However,w es howed that these objections are not firmly founded.…”
Section: Articulation Of the Potential Catalytic Role Of Charge-shiftmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, opposite points of view have appeared and suggested that: 1) CSBs are merely covalent bonds, which exhibit the same orbital shrinkage and kinetic‐energy‐lowering in the bonding region as in H−H, and 2) positive Laplacians simply typify long covalent bonds; hence, the long F–F bond is merely a stretched covalent bond with a positive Laplacian, and the same would be found if we were to stretch H−H . However, we showed that these objections are not firmly founded.…”
Section: How Do We Define a New Class Of Bonding?mentioning
confidence: 99%